2020
DOI: 10.4314/jasem.v24i6.22
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Bacteria and Fungi Associated with Freshwater Fishes from Mijawal River, Nasarawa, Nigeria

Abstract: Understudying the presence of bacteria and fungi population on freshwater fishes, provides the knowledge and understanding of their diversity and potential roles they may play in the health of the aquatic and terrestrial ecosystems. The present study was conducted to evaluate the diversity of bacteria and fungi species of identified fish samples from River Mijawal, Nasarawa State. The fishes were sampled from the only landing for three months (October to December, 2019) for this study. During the sampling peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…A higher result was obtained by Mendoza et al [23] [25]. As well, much lower percentages of 4% and 2.8% were recorded by Adamu et al [26] and El-Kader Mousa-Balabel [27] from fresh water fish in Nigeria (Clarias gariepinus, Labeo senegalensis, and Clarias angularis) and Egypt (O. niloticus), respectively. The difference in results may be attributed to various factors, including differences in geographic location and season, as well as differences in the fish species examined.…”
Section: Disscussionmentioning
confidence: 77%
“…A higher result was obtained by Mendoza et al [23] [25]. As well, much lower percentages of 4% and 2.8% were recorded by Adamu et al [26] and El-Kader Mousa-Balabel [27] from fresh water fish in Nigeria (Clarias gariepinus, Labeo senegalensis, and Clarias angularis) and Egypt (O. niloticus), respectively. The difference in results may be attributed to various factors, including differences in geographic location and season, as well as differences in the fish species examined.…”
Section: Disscussionmentioning
confidence: 77%
“…The results showed that amylolytic bacteria were detected from three different groups, namely Proteus sp., Staphylococcus sp., and Micrococcus sp. Several studies show that these bacteria are bacteria that are often detected in water and can interact in the digestive tract of fish (Adamu et al, 2020). Several information from previous research shows that the Micrococcus sp.…”
Section: Biochemical Testmentioning
confidence: 99%
“…Thus, the contamination of freshwater ecosystems by various anthropogenic activities is becoming an important concern owing to the damage it poses to productivity, environmental sustainability, and social and economic development in Africa (Arimoro and Keke 2016). The activities in the freshwater bodies such as laundry, agricultural operations and hydropower generation introduces pollutants that result in changes observed in the aquatic habitat (Adamu et al, 2020;Adamu et al, 2018;Kun et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Freshwater bodies such as Lakes and reservoirs are valuable resources that possess tremendous economic value as they provide many benefits to nearby settlements, such as means of flood control, recreation, aquatic life support, domestic water supply, irrigation and industrial water supply (Maishanu et al, 2022;KDHE 2011). Monitoring freshwater bodies such as lake helps to create information on species richness in the ecosystem, as well as information on the health status of the water body being studied (Adamu et al, 2020;Ajuzie 2012). Zooplankton such as rotifers, copepods, and cladocerans are environmental stressor indicators and quick responders (Pawlowski et al 2016, Xiong et al 2019.…”
Section: Introductionmentioning
confidence: 99%